2016
DOI: 10.1080/21691401.2016.1228660
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthesis of Cr(III) nanoparticles from electroplating wastewater using chromium-resistant Bacillus subtilis and its cytotoxicity and antibacterial activity

Abstract: The aim of this study was to synthesize and characterize Cr(III) nanoparticles using wastewater from electroplating industries and chromium-resistant Bacillus subtilis. Formation of Cr(III) nanoparticles was confirmed by UV-visible (UV-Vis) spectroscopy at 300 nm. The size of the nanoparticles varied from 4 to 50 nm and energy dispersive spectroscopy profile shows strong Cr peak approximately at 4.45 and 5.2 keV. The nanoparticles inhibited the growth of pathogenic bacteria Staphylococcus aureus and Escherichi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 38 publications
5
3
0
Order By: Relevance
“…No single dose has shown stronger potential than the positive control. Overall, our Cr 2 O 3 NPs have shown potential antibacterial activities against different bacterial strains which are consistent with the previous reports of green nanoparticles (Hassan et al, ; Kanakalakshmi, Janaki, Shanthi, & Kamala‐Kannan, ). The increased antibacterial potential of Cr 2 O 3 NPs is due to the bioactive functional groups attached on the surface of NPs.…”
Section: Resultssupporting
confidence: 92%
“…No single dose has shown stronger potential than the positive control. Overall, our Cr 2 O 3 NPs have shown potential antibacterial activities against different bacterial strains which are consistent with the previous reports of green nanoparticles (Hassan et al, ; Kanakalakshmi, Janaki, Shanthi, & Kamala‐Kannan, ). The increased antibacterial potential of Cr 2 O 3 NPs is due to the bioactive functional groups attached on the surface of NPs.…”
Section: Resultssupporting
confidence: 92%
“…The formation of chromium oxide nanoparticles was confirmed due to the appearance of a strong absorption of electromagnetic wave at 309.87 nm, which is closer to the optical studies of Cr 2 O 3 nanoparticles reported in previous literature [19,20] (Figure 3). The optical band gap was investigated using Tauc plot method, which is a material characterization technique, Tauc plot is used for more intrinsic band gap analysis, which is calculated by famous Tauc equation.…”
Section: Uv-visible Spectroscopysupporting
confidence: 89%
“…The higher Zone of Inhibition in case of K. pneumonia by the chromium oxide nanoparticles synthesized by sol-gel technique was reported earlier [18] and systematic antimicrobial activity of chromium nanoparticles against pathogenic bacteria also reported earlier (Uma et al 2019 and Kanakalakshmi et al 2017. [3,19]…”
Section: Resultssupporting
confidence: 64%